Digitalisasi Materi Pembelajaran Pendidikan Agama Islam dalam Membentuk Karakter Generasi Z yang Islami - Umi Masluhah (EDU-RELIGIA : Jurnal Keagamaan dan Pembelajarannya, 2021)
The increasingly strong use of digital technology has an influence on the world of education, especially generation Z who are referred to as digital natives, meaning that the internet has become a part of life because they have been surrounded by the internet from the womb to the beginning of birth. This research is a qualitative research with a discriptive method of analysis, which will examine the digitalization of learning materials using conventional book media combined with video barcode scans, which later the learning material will become more interesting so that students can understand the message or material conveyed in the video aforementioned. The result of this research is that the digitalization of Islamic Religious Education material at SDI AR Roudhoh is to collaborate learning materials in conventional media packaged in the form of LKS books with digital learning media in the form of sparkol videos or vidioscribes that are broadcast on television or smartphones, and with this learning media students have a high interest in understand the learning material using the media. So that students are able to understand the learning material well and can apply the value of Islamic education in everyday life